Decreased Heart Rate Variability in Individuals With Amyotrophic Lateral Sclerosis - Pimentel, Renata M M; Macedo, Hugo; Valenti, Vítor E [UNESP]; Rocha, Fernando O.; Abreu, Luiz Carlos; de M Monteiro, Carlos Bandeira; Ferreira, Celso (SAGE Publications, 2019)
BACKGROUND: Amyotrophic lateral sclerosis (ALS) is considered a multisystem degenerative disease due to its autonomic dysfunction effects. Autonomic cardiac control disorders can be seen in ALS and influence the quality of life and the life expectancy of affected individuals. We evaluated heart rate variability in subjects with ALS and with variable lung capacity. METHODS: We conducted a prospective cross-sectional study performed in 42 subjects with ALS. The subjects were classified into 2 groups according to their FVC: (FVC > 50% of the predicted value [n = 19] and FVC < 50% of the predicted value [n = 23]). Heart rate was recorded at rest during spontaneous breathing by using a heart rate monitor. Linear indices in the time and frequency domains were analyzed, and non-linear analysis was performed by using Poincaré plots. RESULTS: The results showed a decrease of heart rate variability in the subjects with lower lung capacity and who needed ventilatory support. Qualitative analysis when using the plots supported the quantitative analysis, wherein the group with a lower lung capacity showed reduced heart rate variability. No significant differences were found in the other heart rate variability indices. CONCLUSIONS: The subjects with ALS and with decreased pulmonary capacity had reduced heart rate variability.
Keywords: amyotrophic lateral sclerosis; autonomic nervous system; motor neuron disease; nervous system diseases; respiratory function; spirometry